Colletotrichum crown rot (anthracnose crown rot) of strawberries - Steven MacKenzie; Natalia Peres (EDIS)
PP-238, a 3-page illustrated fact sheet by Steven MacKenzie and Natalia Peres, describes this serious disease of strawberries in warm production region, its causal agent and symptoms, disease development and spread, and control. Includes a table of products labeled for control of colletotrichum crown rot. Published by the UF Department of Plant Pathology, June 2007.